Mini-review Summary - Ronald Osei Mensah; Charles Obeel (Journal of Sociological Research, 2024)
This mini review brings to bear a situation that occurred in the rural areas of West Africa where the inhabitants accused others of being responsible for the loss of their genitals. The town of reference is Zorse, which is inhabited by the Kusasi tribe in the North Eastern part of Ghana. Anthropologists and psychologists explain anxiety assault as a fear reaction that emanates from a people’s belief that a person can cause sex organs to vanish or shrink. Charles Mather used ethnography to describe detailed accounts of happenings. This current paper provides a systematic review of happenings based on the information gathered from the script of Mather. It is revealed that the explanations offered are also grounded in bioengineering and psychology.